Reconstruction of radiation-induced damage in patients with facial hemangiomas using free anterolateral thigh flap - Trần Thiết Sơn; Phan Tuấn Nghĩa; Nguyễn Hữu Trọng; Phạm Thị Việt Dung; Tạ Thị Hồng Thuý; Christopher Runyan (JPRAS Open)
Objective: Radiation therapy to treat hemangiomas is an old method that is no longer used due to its severe side effects. However, in Vietnam, radiotherapy has long been used to treat infantile hemangiomas, which has led to severe sequelae in adulthood. This article shares our experience in reconstructing the sequelae of radiation therapy for facial hemangioma using free anterolateral thigh (ALT) flap. Materials and methods: Six patients underwent facial lesion reconstruction using different ALT flaps, including volume augmentation, fascial, and thinning flaps. Results: The largest flap used was 20 × 8 cm2 and the smallest flap was 11 × 6 cm2. All flaps survived completely and no post-operative complications were noted. The patients were highly satisfied with the surgical outcomes, and the aesthetics of the flap were also excellent, with the flap being similar in color to the facial skin. Conclusion: The ALT flap has several advantages, including flexibility in use, diversity in flap components, and minimal impact on the donor site, making it increasingly popular and effective.